APPLICATION OF THE MARKET PLACE (MP) TYPE COOPERATIVE LEARNING MODEL / SHOPPING FOR MATERIALS WITH POWER POINT MEDIA ON THE MAIN MATERIAL OF FAITH IN THE LAST DAYS IN CLASS VI - Asep Halimursid (Jurnal Scientia, 2022)
Every student in teaching and learning activities has different intelligence. Not all students are able to concentrate and absorb the subject matter at the same time. There are those who have a strong absorption power, there are also those who have moderate or even slow absorption. In this regard, a teacher is required to be careful in choosing a learning model and determine the learning method to be used in conveying subject matter to students. The aims of the study were to find out 1) the effect of applying the market place (MP) method / material expenditure with effective power point can increase learning outcomes 2) to reveal the effect of applying the market place (MP) method / material expenditure with effective power point can increase student learning motivation . This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is the learning outcomes of class VI students at SDN Hegarmanah. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that students' learning achievement increased from cycle I to cycle III, namely, cycle I (25.71%), cycle II (74.14%), and cycle III (88.57%). The conclusion from this study is that the method used by the teacher must be well presented and attract the attention of students, so that students feel happy to learn. The cooperative learning model with market place (MP)/material shopping and also using power point media on the subject matter Faith in the Last Days should not seem to make it difficult for students, but on the contrary it must be able to motivate students to learn more enthusiastically and have fun. and 88.57%